2022
DOI: 10.5888/pcd19.210228
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Severity and Mortality Among Chronic Liver Disease Patients: A Systematic Review and Meta-Analysis

Abstract: Introduction Pre-existing comorbid conditions in COVID-19 patients are risk factors for developing severe disease and death. We aimed to determine the association of chronic liver disease (CLD), a comorbid condition, with severity of disease and death among COVID-19 patients. Methods We searched for studies reporting COVID-19 outcomes among CLD and non-CLD patients in databases including Medline, EMBASE, ScienceDirect, Google Scholar, and Cochrane Library from inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 60 publications
2
38
1
6
Order By: Relevance
“…Krishnan et al [ 30 ] found that CLD patients with elevated AST and tBIL levels had a significantly higher risk fora more severe COVID-19 disease course and also reported that ALD was the most important factor associated with the need for mechanical ventilation. A systematic review including 40 studies, mainly from China, reported that CLD was significantly associated with COVID-19 severity and mortality[ 55 ]. The risk of getting more severe COVID-19 was 2.44 times higher among patients with CLD compared to those without CLD, and the presence of NAFLD was the most strongly associated with higher COVID-19 severity, followed by MAFLD and cirrhosis.…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%
“…Krishnan et al [ 30 ] found that CLD patients with elevated AST and tBIL levels had a significantly higher risk fora more severe COVID-19 disease course and also reported that ALD was the most important factor associated with the need for mechanical ventilation. A systematic review including 40 studies, mainly from China, reported that CLD was significantly associated with COVID-19 severity and mortality[ 55 ]. The risk of getting more severe COVID-19 was 2.44 times higher among patients with CLD compared to those without CLD, and the presence of NAFLD was the most strongly associated with higher COVID-19 severity, followed by MAFLD and cirrhosis.…”
Section: Covid-19 In Patients With Pre-existing Liver Diseasementioning
confidence: 99%
“…Many studies have shown that hospitalized COVID-19 patients with CLD have an acute rise in liver enzymes, which results in a severe condition requiring mechanical ventilation and even leading to death. There are other plausible pathogeneses in patients with cirrhosis who have a worse disease course and even death following COVID-19, such as excess systemic inflammation, intestinal dysbiosis, cirrhosis-induced immune dysfunction, and coagulopathies[ 36 ].…”
Section: Sars-cov-2 Effects On the Livermentioning
confidence: 99%
“…A meta-analysis that focused on the outcome of COVID-19 infection in cirrhotic and non-cirrhotic patients included 40 studies with more than 900,000 participants. This showed that the COVID-19-cirrhosis association had an increased risk for severity (OR = 2.44; 95% CI, 1.89–3.16) and death (OR = 2.35; 95% CI, 1.85–3.00) [ 52 ].…”
Section: Covid-19 and Cirrhosismentioning
confidence: 99%